TESTING THE EFFECTIVENESS OF SOURSOP AND SAPAT LEAF INHIBITORS IN THE PRODUCTION OF RED SUGAR - Dendi Nur Alfianto; Eko Fransisko; Rizky Septika Utami; Mardia Apriani (Fakultas Pertanian Universitas Ratu Samban, 2023)
Sugar palm plants have great potential to be developed as superior plantation commodities. Having many uses of aren can produce various benefits for society. At present, the limited knowledge and skills in managing aren produce low levels of hygiene, especially in producing sap water. On average, palm farmers use excessive preservatives as a mixture to increase the yield of sap water. Thus causing effects that can be harmful to health. Therefore, additional natural ingredients are needed which can inhibit the acidity of the sap water. One of the natural ingredients that can be used are soursop leaves and sapat leaves. The purpose of this research activity is to determine the effectiveness of soursop and safat leaves in inhibiting acid levels in sap water at the right concentration. The experimental design used was a completely randomized design (CRD) with 2 factors, namely the type of inhibiting plants (soursop leaves and sapat leaves) and the concentration (0 ml, 25 ml, 50 ml, 75 ml and 100 ml) given. Parameters observed were pH and time. The results showed that the treatment of sapat leaf extract with a concentration of 100 ml could inhibit the acidity of the sap water.